Impacts of altitude on plant green leaf, fresh litter, and soil stoichiometry in subtropical forests - Zhu, Dehuang; Zhou, Yan; Peng, Suhong; Hua, Weiping; Luo, Bin; Hui, Dafeng (Frontiers in Forests and Global Change, 2024)
Background Ecological stoichiometric characteristics of carbon (C), nitrogen (N), phosphorus (P), and potassium (K) serve as crucial indicators of nutrient cycling and limitation in terrestrial ecosystems. However, our current understanding of stoichiometric characteristics in subtropical forests and their response to different climate conditions is still limited.We selected six altitudes ranging from 700 m to 1200 m to simulate different climate conditions of an evergreen broadleaf forest in Wuyi Mountain, Fujian Province, China. We investigated C, N, P, and K stoichiometry and homeostasis in the green leaves, newly senesced leaf litter (fresh litter), and soil of this forest.Leaf P and K levels showed a decline with increasing altitude. Notably, the stoichiometric ratios in different components exhibited a bimodal distribution along the altitudinal gradient. Additionally, a decline trend of N resorption efficiencies was observed as altitude increased. Moreover, weak homeostasis was observed in P and K in green leaves. These findings highlighted the significant impact of altitude on the stoichiometry in evergreen broadleaf forest. This study also contributed to our understanding of the nutrient cycling mechanism and plant growth strategies of evergreen forests under different climate conditions.